Fascicular Sixth Nerve Palsy as a Presenting Sign of Metastatic Ovarian Carcinoma. Issue 3 (September 2021) - Rohani, Niloufar; Mortensen, Peter; Lee, Andrew G.
Abstract : Abstract: The most common etiology of an isolated abducens nerve palsy in an older adult with vasculopathic risk factors is presumed microvascular ischemia. Because the diagnosis of microvascular ischemia in this setting would not alter patient management, there is debate as to whether further workup is warranted under these circumstances. In this report, we describe a fascicular sixth nerve palsy as the initial presenting sign of metastatic ovarian carcinoma, and we highlight the importance of considering additional workup in select cases of isolated abducens nerve palsies.